Incidence, time of occurrence and response to heart failure therapy in patients with anthracycline cardiotoxicity. Issue 1 (January 2017) - Khan, Arshad A.; Ashraf, Asma; Singh, Rajinder; Rahim, Aadil; Rostom, Walid; Hussain, Mumtaz; Renner, Ian; Collins, Nicholas J.
Abstract : Background: Anthracyclines are commonly used chemotherapeutic medications. Aim: In the current analysis, we evaluated all‐cause mortality and incidence, timing and response to medical therapy of anthracycline cardiotoxicity. Methods: Left ventricular ejection fraction (LVEF) was serially assessed using gated heart pool scan/echocardiography in patients receiving anthracycline‐based chemotherapy from January 2009 to December 2014. Results: A total of 1204 patients was administered anthracyclines during the study period. During a median follow up of 32 (interquartile range: 15–58) months, all‐cause mortality was 38% ( n = 463), with the incidence of cardiotoxicity 10.2% ( n = 123). Only 15.4% ( n = 19) patients required heart failure hospitalisation, with 48% ( n = 59) of patients commenced on beta blockade therapy and/or angiotensin‐converting enzyme inhibitors. The majority of patients (73.2%, n = 90) experienced cardiotoxicity within 1 year of anthracycline initiation. The proportion of patients with complete, partial and no LVEF recovery were 16.3% ( n = 20), 29.3% ( n = 36) and 54.4% ( n = 67) respectively. Mortality was higher in the cardiotoxicity group (49% vs 37%, P < 0.01). History of coronary artery disease, leukaemia, idarubicin use and high cumulative anthracycline dose were predictors of cardiotoxicity. Conclusions: Cardiotoxicity after anthracycline use predictably occurs within the first year of therapy and is dose‐related, with variable degrees of recovery. While the need for hospitalisation for heart failure was uncommon, medical therapy appears underutilised, suggesting there may be a role for improved surveillance and early initiation of treatment.